Flow injection measurement of lead using mercury-free disposable gold-sputtered screen-printed carbon electrodes (SPCE) - Masawat P. (2014)
Screen-printed sensors are promising devices for disposable, cheap and reliable environmental monitoring. In previous studies, workers have used mercury-coated electrodes to allow stripping voltammetry to be performed. In this paper, we describe a disposable sputtered gold sensor which allows underpotential analyte preconcentration and avoids the environmental contamination associated with mercury-based sensors. It is used in combination with a specially fabricated thin-layer flow cell for stripping analysis. The sensor consists of a screen-printed strip with three electrodes; gold coated over carbon-silver ink as the working electrode, silver-silver chloride ink as the pseudo reference electrode, and a carbon-silver ink as the counter electrode. The optimized flow injection (FI) system allows the convenient monitoring of micrograms per litre lead concentrations following short deposition times (detection limit 0.8 μgl-1 at 120 s deposition). The method was evaluated by determining lead in spiked drinking and tap water samples; the recoveries of Pb2+ were 103% (R.S.D. 2.8%) and 97.9% (R.S.D. 7.1%), n = 5, respectively. Measurements in the presence of typical interferences such as copper, cadmium, zinc, iron, chromium, and mercury are reported. © 2003 Elsevier Science B.V. All rights reserved.